State High School Religious Education Teachers ‘Strategies in Minimizing the Occupation of Interreligious Marriages in the Regency of North Minahasa - Nasruddin Yusuf; Mustafa Mustafa (AL-ISHLAH: Jurnal Pendidikan, 2023)
Marriage is said to be valid in the Unitary State of the Republic of Indonesia if it is performed according to their respective religions as regulated in Law Number 16 of 2019 amendment to Law Number 1 of 1974 Concerning Marriage, in Article 2 paragraph (1) which reads "Marriage is lawful, if it is carried out according to the laws of each religion and belief.” However, in reality, there are also many interfaith marriages, either through marriages abroad or through efforts to find legal loopholes. If there are interfaith marriages, this occurs partly due to a lack of knowledge and education when the perpetrators of the marriage are still in school. This research seeks to see the strategies used by Islamic Religious Education teachers in North Minahasa Regency which are considered successful in minimizing the occurrence of interfaith marriages in this region. This research is field research with a qualitative approach and is descriptive-analytical. The results showed that the success of PAI teachers in minimizing interfaith marriages was by implementing two main strategies, namely broadening students' horizons and monitoring and guidance. In broadening students' insights, debgab teaches the concept of responsibility and students' abilities before marriage, explaining religious and government rules that must be obeyed so they are not seen as violating. Meanwhile, the monitoring and guidance strategy is carried out in a limited way for students who are seen as having an affair through dating in the environment of students who are of different religions by identifying the factors that cause this relationship. From the research, it is known that if interfaith marriages occur, then environmental factors are very dominant even though there are also family and behavioral factors but not too significant.